Faktor-Faktor yang Memengaruhi Clinical Outcome Nyeri pada Pasien Diabetes Neuropati di Poliklinik Penyakit Dalam RSUD Kota Yogyakarta - Dirga, Dirga; Nugroho, Agung Endro; Pramantara, Dewa Putu (Jurnal Kefarmasian Indonesia, 2019)
The treatment of diabetic neuropathy pain has not possessed an explicit guideline therapy yet, due to the difference perception towards the respond of pain from certain individu. In indonesia, the data regarding factors that could affect clinical outcome of pain are still limited to the meassurement of tolerance, perception, and sensitivity of certain pain. This study aims to describe the clinical outcome of pain along with the affected factors for diabetic neuropathy patients in Internal Medicine Clinics of Yogyakarta City General Hospital. The design of this This study is an analytical descriptive with cross sectional approach to 81 patients of diabetic neuropathy pain. The pain level measurement of patient is conducted with Visual Analog Scale (VAS) Instrument. The obtained data are analyzed statistically by applying Chi Square and logistical regression analysis. The results of this study showed that 60 patients (74,07%) had reached clinical outcome of pain, and 21 patients (25,93%) had not reached clinical outcome of pain. Factors that affecting clinical outcome of pain to diabetic neuropathy patients were BMI non-obesity (p = 0.043), period of diabetic less than 5 year (p = 0.022), anticonvulsant consuming (p = 0.039), and neurotropic vitamin (p = 0.002). According to the result of multivariate analysis by applying logistical regression test, neurotropic vitamin was claimed as the most influential factor towards clinical outcome of neuropathy pain to diabetic neuropathy patients with p = 0.013, OR = 11.109, and Cl = (1,668-73,970).